PSYCHOLOGY STUDENTS PERSONALITY TRAITS AND MOTIVATION TO CHOOSE STUDIES - Upmane, Anda; Gaitniece-Putāne, Anda; Šmitiņa, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The sample consisted of 83 first course academic and professional psychology program students aged 18-43 years. Research instruments: 1) Demographic survey; 2) BFI (Big Five Inventory, Benet – Martinez & John, 1998), adapted version in Latvian (Austers, 2007); 3) The assessment of psychology studies motivation. Key findings: The most important motivating factors for psychology studies in this sample are interest in psychology and the desire to help. Personality traits are related to the choice of profession motives: Agreeableness and Conscientiousness are positively correlated with the desire to help, Extroversion with a sense of capability for the profession, Neuroticism - with a uncertainity about the right profession choice.